Gingival Diseases in Children and Adolescents - Sulagna Pradhan1 , Sushant Mohanty2 , Sonu Acharya3 , Mrinali Shukla1 , Sonali Bhuyan1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Gingival diseases are prevalent in both children and adolescents. These diseases may or may not be associatedwith plaques, maybe familial in some cases, or may coexist with systemic illness. However, gingiva andperiodontium receive scant attention as the primary dentition does not last for a considerable duration. Asgingival diseases result in the marked breakdown of periodontal tissue, and premature tooth loss affectingthe nutrition and global development of a child/adolescent, precise identification and management ofgingival diseases is of paramount importance. This article comprehensively discusses the nature, spectrum,and management of gingival diseases.